1990
DOI: 10.1002/j.1552-4604.1990.tb03505.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Metoprolol CR/ZOK More Selective Than Conventional Metoprolol and Atenolol?

Abstract: An alternative, simple method to assess beta 1-selectivity is to establish the impact of the beta blocker on beta 2-stimulated increases in plasma glucose and decreases in plasma potassium during an intravenous infusion of terbutaline. In the present study the effects of metoprolol CR/ZOK 100 mg, conventional metoprolol 100 mg, atenolol 100 mg, and placebo on these biochemical changes have been compared. In 12 healthy volunteers, terbutaline infusion of 6 micrograms/kg was administered intravenously over 1 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…Terbutaline infusions offer an opportunity to explore hepatic glucose production in an experimental fashion. Similar to our findings, previous investigations have also reported a dose-related reduction in glucose concentrations with terbutaline stimulation and concomitant β-blocker administration 17, 19. Carvedilol is non-selective, and metoprolol is β 1 selective at lower doses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Terbutaline infusions offer an opportunity to explore hepatic glucose production in an experimental fashion. Similar to our findings, previous investigations have also reported a dose-related reduction in glucose concentrations with terbutaline stimulation and concomitant β-blocker administration 17, 19. Carvedilol is non-selective, and metoprolol is β 1 selective at lower doses.…”
Section: Discussionsupporting
confidence: 92%
“…Carvedilol is non-selective, and metoprolol is β 1 selective at lower doses. Previous studies reported that metoprolol is less β 1 selective at higher doses 17. According to their adrenergic receptor blocking pharmacology, one would anticipate more pronounced reduction of glucose AUC by carvedilol due to its non-selectivity and affinity to β 2 receptors 20.…”
Section: Discussionmentioning
confidence: 96%
“…However, at higher plasma concentrations even selective ~-blockers begin to block ~2-receptors. Thus, for example, the terbutaline-induced ~2-mediated fall in plasma potassium levels due to increased uptake into cells is blocked more by higher concentrations of a selective drug like metoprolol than by lower plasma concentrations (Kendall et al 1990;Smith et al 1983). Furthermore, at higher concentrations of selective agents the relative bronchosparing effects begin to be lost (Lofdahl et al 1988).…”
Section: Adverse Effectsmentioning
confidence: 95%
“…In a study of 1-selectivity, terbutaline infusions were given to 12 healthy subjects and 2-stimulated increase in plasma glucose and decrease in potassium were measured after pretreatment with metoprolol CR/ZOK (100 mg), conventional metoprolol (100 mg) and atenolol (100 mg) (29). All three -blockers decreased the peak plasma-glucose level compared with placebo, but the reduction was significantly less with metoprolol CR/ZOK compared to atenolol.…”
Section: Clinical 1-selectivity and Plasma Peak Concentrationmentioning
confidence: 99%